IoT- Based Intelligent System for Farm Electric Fence - Yunus, Muhamad Adeeb Bin Yunus; Dr Mohd Shamian Bin Zainal (Progress in Engineering Application and Technology, 2023)
When humans or animals encounter a solar fence, they receive a brief yet powerful jolt. The shock provides a deterring impact while preventing any loss of life. The issue is that severed electrical cables may go unrepaired because of the electric fences constructed near secluded woods, farmers frequently replace the batteries that power electric fences. The objective of this study is to design an electric fence system prototype following a minimum safety standard. This study proposes an IoT-based electric fence notification system that enables farmers to monitor the state of the fence from their smartphones with a monitoring system to monitor the condition of the electric fence. The initial component is a traditional electric fence, consisting of a solar panel, solar controller, 12V battery, energizer, copper earth rod, and aluminum wire. The other component of this system is a control and monitoring box for the Internet of Things. A 2015 Journal of Wildlife Management study examined the use of electric fences to keep white-tailed deer away from agricultural harvests. The investigation discovered that electric fencing reduced deer browsing damage by 95% on average. Other than that, in other study shows electric fencing was significantly effective in reducing crop damage by 78% and livestock depredation by 30%–60%.[3]